Analysis of the fractional descriptor linear systems by the decomposition into the dynamical and static parts - Tadeusz Kaczorek; Lukasz Sajewski (Archives of Control Sciences, 2024)
A new method of the decomposition of the fractional descriptor linear continuoustime and discrete-time systems into dynamical and static parts is proposed. Conditions for the decomposition of the fractional descriptor linear systems are established and procedures for compositions of the matrices of dynamical and static parts are given. The procedures are illustrated by numerical examples.